Kedudukan UsïªÅ«l Fiqh dalam Pengembangan Metodologi Ekonomi Islam - Faozan, Akhmad (STAIN Salatiga, 2010)
UsïªÅ«l fiqh as a methodology of islamic law is rooted from al-Qurâan and Sunnah. But text of al-Qurâan and Sunnah is a little bit give speaking of methodology, even only give an indication from which syariah law can be deducted in order to order islamic teaching in the sphere of economic problem, such methodology need to elaborated. But al-Qurâan, Sunnah and Ijtihad, remained to priority guidence in the development of islamic economic methodologies. Even, maxims of usïªÅ«l fiqh such as qiyÄs, istihï§sÄn and maslahah when did so fourth can be used to develop the methodology of islamic economic. Keywords: UsïªÅ«l fiqh, Development, Methodology of Islamic Economic.